Does daily co administration of gonadotropins and letrozole during the ovarian stimulation improve IVF outcome for poor and sub optimal responders? - Moran Shapira; Raoul Orvieto; Oshrit Lebovitz; Ravit Nahum; Adva Aizer; Aliza Segev-Zahav; Jigal Haas (BMC, 2020)
Abstract Background Co-administration of letrozole during the first 5 days of ovarian stimulation was suggested to improve IVF outcomes in poor responders. We aimed to determine whether poor/sub-optimal responders might benefit from Letrozole co-treatment throughout the entire stimulation course. Methods We retrospectively reviewed the medical files of women who demonstrated poor (oocyte yield ≤3) and sub-optimal (4 ≤ oocyte yield ≤9) ovarian response during conventional multiple-dose antagonist stimulation protocols and were co-treated in a subsequent cycle with 5 mg Letrozole from the first day of stimulation until trigger day. A self-paired comparison between gonadotropins-only and gonadotropins-letrozole cycles was performed. Results Twenty-four patients were included. Mean patients' age was 39.83 ± 4.60 and mean day-3-FSH was 12.77 ± 4.49 IU/m. Duration of stimulation and total gonadotropins dose were comparable between the two cycle groups. Peak estradiol levels were significantly lower in gonadotropins-letrozole cycles (2786.74 ± 2118.53 vs 1200.13 ± 535.98, p < 0.05). Number of retrieved oocytes (3.29 ± 2.15 vs 6.46 ± 3.20, p < 0.05), MII-oocytes (2.47 ± 1.65 vs 5.59 ± 3.20, p < 0.05), 2PN-embryos (1.78 ± 1.50, 4.04 ± 2.74, p < 0.05) and top-quality embryos (0.91 ± 0.97 vs. 2.35 ± 1.66, p < 0.05) were significantly higher in the gonadotropins-letrozole cycles. Clinical pregnancy rate in gonadotropins-letrozole cycles was 31.5%. Conclusion Letrozole co-treatment during the entire stimulation course improves ovarian response and IVF outcomes in poor/sub-optimal responders.